A Solution To The Problem Of Scheduling And Replacement In Open-Pit Mines - Qing Wang (Society for Mining, Metallurgy & Exploration, 1989)
A longterm overburden removal plan can be realistic and optimum only when the cost and capacity profiles off the equipment assigned to the operation are taken into consideration. Therefore, the planning should involve the proper assignment of equipment capacity by insuring a timely investment and a timely replacement policy throughout the mine life. A dynamic solution algorithm has been developed, by which all possible truck fleet alternatives are evaluated for each year off the operation. Cumulative cost off the operation is carried throughout the analysis. The optimum solution is obtained by selecting the minimum cumulative cost at the last year and tracing backward the best fleet alternative for each year. The solution provides: 1. the optimum amount of overburden to be removed each year; 2. the best fleet to be assigned to the job; and 3. the best equipment replacement policy.